Boosting the Photovoltaic Performance and Thermal Stability of Organic Solar Cells via an Insulating Fluoropolymer Additive. Issue 7 (3rd May 2022) - Zeng, Hang; Hu, Cetao; Wu, Di; Xia, Jianlong
Abstract: The use of processing additives is one of the most widely used approaches to optimizing the bulk heterojunction (BHJ) morphology for boosting the photovoltaic performance of organic solar cells (OSCs). Recently, insulating polymer‐based additives have drawn great attention owing to the merits of good morphology‐directing abilities, simple post treatments, rich functionality and enhanced device stabilities. In this contribution, a known fluoropolymer poly‐ p ‐trifluoromethylstyrene (PTFS) is selected as a solid additive. Employing PTB7‐Th:PDI2 (ethylene‐annulated perylene diimide dimer) as the prototype active layer, the devices processed with PTFS shows a best power conversion efficiency (PCE) of 6.64 %, which is the highest efficiency for nude PDI2‐based OSCs. For comparison, the photovoltaic performance OSCs processed with polystyrene (PS) or without additive were investigated, PCEs of 5.29 % and 5.76 % were obtained, respectively. It is worth noting that the utilization of PTFS can also improve the thermal stability of the devices pronouncedly. Moreover, PTFS based additive also displays enhanced performance in other devices with different active layers, illustrating a good universality in OSCs. The enhancement of the PCE and thermal stability may result from the relatively lower surface energy of PTFS, which can boost the light absorbance capability as well as promote a favorable phase separation of the active layer. Abstract : A known fluoropolymer poly‐ p‐ trifluoromethylstyrene (PTFS) is selected as a solid additive. With addition of PTFS, a best PCE of 6.64 % was obtained for devices using PTB7‐Th:PDI2 as the prototype active layer. Moreover, the addition of PTFS can also improve the thermal stability of the devices pronouncedly and displays a good universality in OSCs.